Bacterial anomalies associated with deep sea hydrocarbon seepage along the Scotian Slope. (March 2023) - Li, Carmen; Adebayo, Oyeboade; Ferguson, Deidra K.; Wang, Scott; Rattray, Jayne E.; Fowler, Martin; Webb, Jamie; Campbell, Calvin; Morrison, Natasha; MacDonald, Adam; Hubert, Casey R.J.
Abstract: Deep sea hydrocarbon seep detection relies predominantly on geochemical analyses of seabed marine sediment cores to identify the presence of gas or oil. The presence of seeping hydrocarbons in these locations alters local redox stratification and microbial community structure. Cultivation-independent biodiversity surveys of microbial communities can offer a proxy for seeping hydrocarbons, but this strategy has not been extensively investigated in deep water settings. In this study, 16S rRNA gene sequencing of bacterial communities was performed on sediment cores obtained in >2500 m water depth at 43 different locations in the Northwest Atlantic Ocean. Cores extending down to 10 m below seafloor (mbsf) were assessed for gas composition, gas isotopes and liquid hydrocarbons. Over 650 bacterial biodiversity libraries were constructed from different sediment depths at these locations. Sites with strong evidence for the presence of thermogenic or biogenic hydrocarbon seepage were reflected in bacterial population analyses that revealed significant differences between hydrocarbon seep and non-seep locations. Specific bacterial indicators were associated with different sediment depth intervals including Caldatribacteriota and Campilobacterota OTUs observed in high relative sequence abundance at 20-50 cmbsf in hydrocarbon seep sediments. These groups were differentially abundant between sites with thermogenic and biogenic hydrocarbon seepage. Highlights: Extensive bacterial biodiversity survey of deep sea sediments to complement hydrocarbon geochemistry Bacterial community composition varies with sediment depth and presence of hydrocarbon seepage Specific uncultured bacteria associate with biogenic and thermogenic hydrocarbon geofluids DNA based sediment surveys offer increased capacity to locate thermogenic seep sites